Hubungan Antara Minat Terhadap Pekerjaan dengan Kepuasan Kerja pada Karyawan Perusahaan X di Yogyakarta - MRA Puspitasari; Hendra Dwi Saputra (LPPM Universitas Proklamasi 45, 2021)
The purpose of this study is to determine the relationship between work interest and job satisfaction in employee of Perusahaan X Yogyakarta. This study uses a quantitative method that analyzes using non-parametric statistical analysis of Carl Pearson correlation. In determining the number of sample, researchers used cluster random sampling. The sample of this study is 70 employees in Perusahaan X Yogyakarta. Research data collection uses the scale of work interest and job satisfaction. The work interest has a value of cronbach alpha (α) 0.938 with 40 valid items and job satisfaction has a value of cronbach alpha (α) 0.956 with 36 valid items.Based on the results of statistical test, this study obtained a negative correlation coefficient (rxy) 0.628 with a significance level of 0.000 (p < 0.01), this shows that there is a significant positive relationship between work interest and job satisfaction. That means, the positive work interest, the job satisfaction improve. The average of the work interest of the subjects is in the positive category and job satisfaction of the subjects in the higher category. The effective contribution of work interest to job satisfaction is 62.8% whilst 37.2% is contributed by other factors outside of this research.